ESTUDO DA EVOLUÇÃO MICROESTRUTURAL DO COMPÓSITO METÁLICO USANDO LIGNINAS EXTRAÍDA DA MADEIRA - FERNANDES, Hedielle Brasil; DE SOUZA, Armando Cirilo; ROSSI, Jesualdo Luiz; OLIVEIRA, Rony Gonçalves; GOUVÊA, Adriana de Fátima Gomes (ANAIS DO ENIC, 2017)
-